2021
DOI: 10.1111/acem.14347
|View full text |Cite
|
Sign up to set email alerts
|

The impact of racism on emergency health care workers

Abstract: Although racism is a constant reality and threat for many, the deaths of George Floyd, Ahmaud Arbery, and Breonna Taylor and the civil movement against systemic racism that followed were significant sources of stress in 2020. 1 Racism can be classified into three levels: personally mediated, internalized, and systemic or institutionalized. 2 Personally mediated racism is defined as "prejudice and discrimination." 2 Internalized racism is the "acceptance by members of the stigmatized races of negative messages"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Even in the absence of physical assault, verbal abuse can be distressing in its own right, especially if the abuse targets personal or cultural identities, such as race, gender, or sexual orientation. Previous research among healthcare workers has identified that harassment from patients on these grounds is both widespread and contributes to insomnia, depression, anxiety, burnout, attrition from healthcare, and suicide [19,20]-problems that have increased since the onset of the COVID-19 pandemic [21][22][23][24]. Unfortunately, the problem of under-reporting [17] means that there is a lack of similar evidence on nonphysical violence against paramedics, creating a gap in research with potentially significant implications for the health and retention of the workforce.…”
Section: Non-physical Violencementioning
confidence: 99%
“…Even in the absence of physical assault, verbal abuse can be distressing in its own right, especially if the abuse targets personal or cultural identities, such as race, gender, or sexual orientation. Previous research among healthcare workers has identified that harassment from patients on these grounds is both widespread and contributes to insomnia, depression, anxiety, burnout, attrition from healthcare, and suicide [19,20]-problems that have increased since the onset of the COVID-19 pandemic [21][22][23][24]. Unfortunately, the problem of under-reporting [17] means that there is a lack of similar evidence on nonphysical violence against paramedics, creating a gap in research with potentially significant implications for the health and retention of the workforce.…”
Section: Non-physical Violencementioning
confidence: 99%
“…Even absent a physical assault, verbal abuse can be distressing in its own right, especially if the abuse targets personal or cultural identities, such as race, gender, or sexual orientation. Previous research among healthcare workers has identified that harassment from patients on these grounds contributes to insomnia, depression, anxiety, burnout, attrition from health care, and suicide [19,20] problems that have increased since the onset of the COVID-19 pandemic [21][22][23][24]. There is, then, a compelling need to study and respond to all forms of violence against paramedics, particularly those that are the least likely to be documented or reported.…”
Section: Non-physical Violencementioning
confidence: 99%
“…These factors may have impacted the overall levels of stress felt by FHCWs during the COVID-19 pandemic. For instance, one survey found that 30% of healthcare workers were at least moderately distressed by systemic racism in August-September 2020 [ 12 ]. To date, however, whether racism-related distress may be associated with mental health treatment utilization among FHCWs has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%